Editorial Introduction to LACLIL 5(1), April 2012 - Carl Edlund Anderson (Universidad de La Sabana, 2012)
It is with great pleasure that I welcome you to a new issue of the Latin American Journal of Content and Language Integrated Learning (LACLIL), offering insights on the theory and practice of CLIL-based approaches from practitioners and researchers in Latin America and around the world.